Air pollution exposure and lung function in highly exposed subjects in Beijing, China: a repeated-measure study - Baccarelli, Andrea A; Zheng, Yinan; Zhang, Xiao; Chang, Dou; Liu, Lei; Wolf, Katherine Rose; Zhang, Zhou; McCracken, John P; Díaz, Anaité; Bertazzi, Pier Alberto; Schwartz, Joel; Wang, Sheng; et al. (Particle and fibre toxicology, 2014)
Exposure to ambient particulate matter (PM) has been associated with reduced lung function. Elemental components of PM have been suggested to have critical roles in PM toxicity, but their contribution to respiratory effects remains under-investigated. We evaluated the effects of traffic-related PM(2.5) and its elemental components on lung function in two highly exposed groups of healthy adults in Beijing, China. The Beijing Truck Driver Air Pollution Study (BTDAS) included 60 truck drivers and 60 office workers evaluated in 2008. On two days separated by 1-2 weeks, we measured lung function at the end of the work day, personal PM(2.5), and nine elemental components of PM(2.5) during eight hours of work, i.e., elemental carbon (EC), potassium (K), sulfur (S), iron (Fe), silicon (Si), aluminum (Al), zinc (Zn), calcium (Ca), and titanium (Ti). We used covariate-adjusted mixed-effects models including PM(2.5) as a covariate to estimate the percentage change in lung function associated with an inter-quartile range (IQR) exposure increase. The two groups had high and overlapping exposure distributions with mean personal PM(2.5) of 94.6 μg/m³ (IQR: 48.5-126.6) in office workers and 126.8 μg/m³ (IQR: 73.9-160.5) in truck drivers. The distributions of the nine elements showed group-specific profiles and generally higher levels in truck drivers. In all subjects combined, forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) did not significantly correlate with PM(2.5). However, FEV1 showed negative associations with concentrations of four elements: Si (-3.07%, 95% CI: -5.00; -1.11, IQR: 1.54), Al (-2.88%, 95% CI: -4.91; -0.81, IQR: 0.86), Ca (-1.86%, 95% CI: -2.95; -0.76, IQR: 1.33), and Ti (-2.58%, 95% CI: -4.44; -0.68, IQR: 0.03), and FVC showed negative associations with concentrations of three elements: Si (-3.23%, 95% CI: -5.61; -0.79), Al (-3.26%, 95% CI: -5.73; -0.72), and Ca (-1.86%, 95% CI: -3.23; -0.47). In stratified analysis, Si, Al, Ca, and Ti showed associations with lung function only among truck drivers, and no significant association among office workers. Selected elemental components of PM(2.5) showed effects on lung function that were not found in analyses of particle levels alone.